1999
DOI: 10.7589/0090-3558-35.4.796
|View full text |Cite
|
Sign up to set email alerts
|

Tuberculosis in a Wild Subantarctic Fur Seal from Argentina

Abstract: The first case of tuberculosis is described in a wild subantarctic fur seal (Arctocephalus tropicalis) found on the Argentine coast. There was hydrothorax and white firm granulomatous lesions of 40-50 mm in diameter in the lungs. Lesions consisted of a central area of caseous necrosis, an intermediate zone of epithelioid and lymphocytic mononuclear cells, and a peripheral zone of connective tissue. Biochemical and drug sensitivity tests and inoculation of Guinea pigs confirmed the identification as Mycobacteri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
32
0
4

Year Published

2004
2004
2023
2023

Publication Types

Select...
5
3
2

Relationship

1
9

Authors

Journals

citations
Cited by 53 publications
(37 citation statements)
references
References 6 publications
0
32
0
4
Order By: Relevance
“…According to the literature, the most frequently affected pinniped species has been the Southern sea lion (Otaria flavescens), the majority of which has been kept in captivity. The lesions found in the animals comprised mainly of nodular granulomatous lesions with caseation in lung and thoracic lymph nodes, thus indicating the respiratory tract as the most likely route of infection in most of the ani-mals (Forshaw and Phelps, 1991;Cousins et al, 1993;Woods et al, 1995;Bernardelli et al, 1996;Thorel et al, 1998;Bastida et al, 1999;Cousins et al, 2003).…”
mentioning
confidence: 99%
“…According to the literature, the most frequently affected pinniped species has been the Southern sea lion (Otaria flavescens), the majority of which has been kept in captivity. The lesions found in the animals comprised mainly of nodular granulomatous lesions with caseation in lung and thoracic lymph nodes, thus indicating the respiratory tract as the most likely route of infection in most of the ani-mals (Forshaw and Phelps, 1991;Cousins et al, 1993;Woods et al, 1995;Bernardelli et al, 1996;Thorel et al, 1998;Bastida et al, 1999;Cousins et al, 2003).…”
mentioning
confidence: 99%
“…A tuberculose causada pelo complexo Mycobacterium tuberculosis é uma enfermidade em ascensão nas colônias naturais e em cativeiro de pinípedes do Hemisfério Sul (BASTIDA et al, 1999;BERNARDELLI et al, 1996;COUSINS et al, 1993;PHELPS, 1991;WOODS et al, 1995).…”
Section: Enfermidades Bacterianasunclassified
“…Pinnipeds arriving on Brazilian beaches are invariably exhausted and sick, and Velozo et al (2009) concluded that these feeble animals tend to develop diseases such as tuberculosis due to their diminished immunological capacity. Tuberculosis was first confirmed by Bastida et al (1999) (Bernardelli et al 1996). In addition, Blanc et al (2009) first reported about influenza viruses A and B circulation in A. australis from Uruguay.…”
mentioning
confidence: 97%